Process for the preparation of a polymer viscosifier for fracturing
Patent Information
- Application Number
- CN202511703452.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-19
- Publication Date
- 2026-09-08
- Estimated Expiration
- 2045-11-19
AI Technical Summary
上述制备的粘弹性颗粒驱油剂一是抗剪切性能不足,二是只能应用于<95℃的油藏
(1)本发明所述的压裂用聚合物稠化剂的制备方法,以丙烯酰胺为主单体,以马来酸单[2(1-氧-2-丙烯基)氧乙基]酯、甲基丙烯酸(三乙氧基硅基)甲酯以及2-[[2-(甲基丙烯酰氧基)乙基]二甲铵]乙酸盐为功能单体,以氧化还原引发剂结合偶氮引发剂作为引发剂体系,通过梯度温度聚合实现多单体共聚,制备得到具有耐温以及抗盐性能的压裂用聚合物稠化剂。
Smart Images

Figure SMS_13 
Figure SMS_14 
Figure SMS_15
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer thickener preparation technology, specifically relating to a method for preparing a polymer thickener for fracturing. Background Technology
[0002] Fracturing is a crucial technology for the efficient and large-scale development of unconventional oil and gas (tight oil and gas, shale oil and gas, coalbed methane, etc.), low-permeability, and deep oil and gas resources. Fracturing fluid is an essential chemical working fluid used in the fracturing process, playing a vital role in reducing operational friction, creating complex fracture networks, and efficiently carrying proppant to connect the fracture network. Its performance significantly impacts the final stimulation effect and oil and gas recovery rate. Thickeners, as key components of fracturing fluids, are particularly critical in terms of their temperature resistance and salt tolerance, ensuring the drag reduction and proppant carrying performance of the fracturing fluid system.
[0003] Thickeners mainly fall into three categories: natural polymers, biopolymers, and synthetic polymers. Currently, synthetic polymer thickeners are widely used due to their wide availability and advantages such as strong thickening properties, excellent temperature resistance, low residue rate, good sand-carrying capacity, simple synthesis process, and low cost.
[0004] Patent CN101775275B discloses a viscoelastic particle oil displacement agent and its preparation method. The method involves dissolving 100 parts of acrylamide in 150-180 parts of deionized water to prepare an aqueous solution, dissolving 0.35-0.5 parts of dimethylaminoethyl methacrylate in 20-40 parts of water to prepare a solution, and dissolving 0.03-0.05 parts of sodium bisulfite in 30-50 parts of water to prepare an aqueous solution. These solutions are sequentially added to a reaction vessel equipped with a stirrer, thermometer, and reflux condenser. After deoxygenating with nitrogen at 25-30°C for 15 minutes, 0.03-0.05 parts of potassium persulfate aqueous solution dissolved in 30-50 parts of water are added. The mixture is stirred at low speed under nitrogen protection. After the system gels, it is kept at this temperature for 2-4 hours. The product is then cut into pieces, dried, pulverized, and sieved to obtain the viscoelastic particle oil displacement agent. However, the viscoelastic particle oil displacement agent prepared in this way has two drawbacks: insufficient shear resistance and applicability only to reservoirs with temperatures below 95°C.
[0005] Therefore, it is necessary to explore a new type of polymer thickener for fracturing. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing a polymer thickener for fracturing, wherein the polymer thickener prepared by this method has excellent temperature resistance, salt resistance and shear resistance.
[0007] The preparation method of the polymer thickener for fracturing according to the present invention comprises the following steps: (1) Add anhydrous sodium sulfate to methyl methacrylate (triethoxysilyl) and stir for 4-4.5 hours, then filter to prepare pretreated methyl methacrylate (triethoxysilyl) and mix it with anhydrous ethanol to prepare a pretreated methyl methacrylate (triethoxysilyl) solution. (2) Mix 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate with deionized water, then add sodium bicarbonate solution to adjust the pH of the system to 7.0, and purge with nitrogen to remove oxygen, to prepare a pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution; (3) Under nitrogen purging, deionized water was added to the reaction vessel, followed by the addition of acrylamide, maleic acid mono[2(1-oxo-2-propenyl)oxyethyl] ester, pretreated methacrylate (triethoxysilyl) methyl ester solution, and pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate solution. The mixture was stirred until completely dissolved to obtain an aqueous phase. (4) Under a nitrogen atmosphere, the aqueous phase reaction temperature prepared in step (3) is controlled at 13-15℃. Then, the azo initiator solution is added at once and stirred for 30-35s. Then, the ammonium persulfate solution is added at once and stirred for 30-35s. Finally, the sodium bisulfite solution is added at once and stirred for 30-35s. Nitrogen gas is stopped. The reaction system is heated to 80-82℃ and kept at that temperature for 2h. Then, the temperature is lowered to 58-60℃ and kept at that temperature for 4h. After the reaction is completed, the polymer thickener for fracturing is prepared by post-treatment. The molar ratio of acrylamide in step (3), maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester, pretreated methacrylate (triethoxysilyl) methyl methacrylate in step (1), and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate in step (2) is 1.4-1.5 : 0.1-0.2 : 0.2-0.3 : 0.15-0.2.
[0008] In step (1), the mass ratio of methyl methacrylate (triethoxysilyl) to anhydrous sodium sulfate is 2:1.
[0009] In step (1), the CAS number of methyl methacrylate (triethoxysilyl) is 5577-72-0, and its structural formula is [insert structural formula here]. .
[0010] In step (1), anhydrous ethanol and pretreated methyl methacrylate (triethoxysilyl) are mixed evenly at a mass ratio of 1:2 to prepare a pretreated methyl methacrylate (triethoxysilyl) solution.
[0011] In step (2), 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate and deionized water are stirred at 200 r / min for 5-7 min at room temperature in a mass ratio of 1:0.7. Then, a 5% sodium bicarbonate solution is added to adjust the pH of the system to 7.0. Nitrogen gas is then purged for 30-35 min to remove oxygen, thus preparing a pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution.
[0012] In step (2), the CAS number of 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate is 62723-61-9, and its structural formula is […]. .
[0013] In step (3), the CAS number of maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester is 19201-36-6, and its structural formula is as follows: .
[0014] In step (3), the mass ratio of acrylamide, maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester, pretreated methacrylate (triethoxysilyl) methyl methacrylate in step (1), and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate in step (2) to deionized water in step (3) is 1:4.
[0015] In step (3), the stirring speed is 200 r / min. Add acrylamide and stir until completely dissolved. Then add maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester and continue stirring for 5-7 min. Add pretreated methyl methacrylate (triethoxysilyl) solution and stir for 5-7 min. The addition time is controlled at 4-5 min. Finally, add pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution and stir for 5-7 min until completely dissolved.
[0016] The azo initiator solution in step (4) is prepared by mixing 2,2'-azobis(2-methylpropylimidazolium) hydrochloride with deionized water to obtain a 1% mass concentration 2,2'-azobis(2-methylpropylimidazolium) hydrochloride solution.
[0017] The ammonium persulfate solution mentioned in step (4) is prepared by mixing ammonium persulfate and deionized water evenly to obtain an ammonium persulfate solution with a mass concentration of 3%, and then purging with nitrogen gas for 5 minutes to remove oxygen.
[0018] The sodium bisulfite solution mentioned in step (4) is prepared by mixing sodium bisulfite with deionized water to obtain a sodium bisulfite solution with a mass concentration of 1.6%, and then purging with nitrogen gas for 5 minutes to remove oxygen.
[0019] In step (4), the molar ratio of ammonium persulfate in the ammonium persulfate solution to sodium bisulfite in the sodium bisulfite solution is 1:1.2, and the molar ratio of 2,2'-azobis(2-methylpropylimidazolium) hydrochloride in the azo initiator solution to ammonium persulfate in the ammonium persulfate solution is 0.11:1.
[0020] The molar ratio of acrylamide in step (3) to ammonium persulfate in the ammonium persulfate solution in step (4) is 1:0.0008.
[0021] In step (4), the temperature is increased to 80-82℃ at a rate of 2℃ / min and held for 2 hours, and then decreased to 58-60℃ at a rate of 1.5℃ / min and held for 4 hours.
[0022] The post-treatment described in step (4) involves pouring the reaction solution into acetone while it is still hot, with a volume ratio of 1:3 between the reaction solution and acetone, so that the polymer precipitates out. Then, it is allowed to stand at room temperature for 30-35 minutes, filtered, washed three times with acetone, and finally vacuum dried at 55-60℃ and -0.09MPa for 8 hours. The mixture is then pulverized through an 80-mesh sieve to prepare the polymer thickener for fracturing.
[0023] Compared with the prior art, the present invention has the following advantages: (1) The preparation method of the fracturing polymer thickener of the present invention uses acrylamide as the main monomer, maleic acid mono[2(1-oxo-2-propenyl)oxyethyl] ester, methyl methacrylate (triethoxysilyl) and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate as functional monomers, and a redox initiator combined with an azo initiator as the initiator system. The multi-monomer copolymerization is achieved by gradient temperature polymerization to prepare a fracturing polymer thickener with temperature resistance and salt resistance.
[0024] (2) The preparation method of the polymer thickener for fracturing described in this invention uses acrylamide as the main monomer and maleic acid mono[2(1-oxo-2-propenyl)oxyethyl] ester, methyl methacrylate (triethoxysilyl) ester, and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate as functional monomers. The four monomers are polymerized to prepare the polymer thickener. Among them, the carboxylate anion in the maleic acid mono[2(1-oxo-2-propenyl)oxyethyl] ester molecule can enhance the hydrophilicity of the prepared polymer thickener through hydration, ensuring the solubility of the polymer in water. At the same time, the two double bonds in the molecular structure provide crosslinking sites for the polymerization reaction. In addition, the ester group structure in the molecular structure helps to suppress the random thermal motion of the molecular chain at high temperature, reduce chain segment coiling, and improve the shear stability and thermal stability of the polymer. The siloxane groups in the molecular structure of methyl methacrylate (triethoxysilyl) enhance the polymer's temperature and shear resistance. Firstly, the siloxane groups introduced into the polymer backbone inhibit chain breakage and degradation at high temperatures, improving thermal stability. Secondly, in an aqueous environment, the siloxane groups slowly hydrolyze to generate silanols, which further condense to form Si-O-Si covalent bonds, constructing a uniformly dispersed "organic backbone-inorganic silicon oxide" hybrid network structure. This rigid network not only strengthens the overall structural strength of the polymer and resists shear forces that damage the molecular chains, but also restricts the thermal motion of the organic backbone through steric hindrance, further improving thermal stability. The 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate molecule contains both quaternary ammonium cations and carboxylate anions, forming an electrically neutral inner salt structure. The balanced distribution of positive and negative charges within the molecule prevents the salt ions from significantly compressing the electric double layer of the polymer molecular chain. At the same time, there is a weak charge repulsion between the inner salt groups on adjacent molecular chains, which allows the molecular chain to maintain an extended conformation under high salinity conditions, thereby improving the salt resistance of the polymer. Thus, the synergistic effect among the four monomers gives the prepared polymer thickener salt resistance, temperature resistance, and shear resistance.
[0025] (3) The preparation method of the polymer thickener for fracturing described in this invention is simple, the parameters are easy to control, and the prepared polymer thickener has stable performance and is suitable for fracturing operations in oil and gas wells under high temperature and high salt conditions. Detailed Implementation
[0026] Example 1 The preparation method of the polymer thickener for fracturing described in Example 1 consists of the following steps: (1) Add anhydrous sodium sulfate to methyl methacrylate (triethoxysilyl) and stir for 4.3 hours, then filter to prepare pretreated methyl methacrylate (triethoxysilyl) and mix it with anhydrous ethanol to prepare a pretreated methyl methacrylate (triethoxysilyl) solution. (2) Mix 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate with deionized water, then add sodium bicarbonate solution to adjust the pH of the system to 7.0, and purge with nitrogen to remove oxygen, to prepare a pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution; (3) Under nitrogen purging, deionized water was added to the reaction vessel, followed by the addition of acrylamide, maleic acid mono[2(1-oxo-2-propenyl)oxyethyl] ester, pretreated methacrylate (triethoxysilyl) methyl ester solution, and pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate solution. The mixture was stirred until completely dissolved to obtain an aqueous phase. (4) Under a nitrogen atmosphere, the aqueous phase reaction temperature prepared in step (3) is controlled at 14°C. Then, the azo initiator solution is added at once and stirred for 33s. Then, the ammonium persulfate solution is added at once and stirred for 33s. Finally, the sodium bisulfite solution is added at once and stirred for 33s. Nitrogen gas is stopped. The reaction system is heated to 81°C and kept at that temperature for 2h. Then, the temperature is lowered to 59°C and kept at that temperature for 4h. After the reaction is completed, the polymer thickener for fracturing is prepared by post-treatment. The molar ratio of acrylamide in step (3), mono[2(1-oxo-2-propenyl)oxoethyl] maleate, pretreated methyl methacrylate (triethoxysilyl) in step (1), and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate in step (2) is 1.45 : 0.15 : 0.25 : 0.17.
[0027] In step (1), the mass ratio of methyl methacrylate (triethoxysilyl) to anhydrous sodium sulfate is 2:1.
[0028] In step (1), the CAS number of methyl methacrylate (triethoxysilyl) is 5577-72-0, and its structural formula is [insert structural formula here]. .
[0029] In step (1), anhydrous ethanol and pretreated methyl methacrylate (triethoxysilyl) are mixed evenly at a mass ratio of 1:2 to prepare a pretreated methyl methacrylate (triethoxysilyl) solution.
[0030] In step (2), 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate and deionized water were stirred at 200 r / min for 6 min at room temperature in a mass ratio of 1:0.7. Then, a 5% sodium bicarbonate solution was added to adjust the pH of the system to 7.0. Nitrogen gas was then purged for 33 min to remove oxygen, thus preparing a pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution.
[0031] In step (2), the CAS number of 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate is 62723-61-9, and its structural formula is […]. .
[0032] In step (3), the CAS number of maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester is 19201-36-6, and its structural formula is as follows: .
[0033] In step (3), the mass ratio of acrylamide, maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester, pretreated methacrylate (triethoxysilyl) methyl methacrylate in step (1), and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate in step (2) to deionized water in step (3) is 1:4.
[0034] In step (3), the stirring speed is 200 r / min. Add acrylamide and stir until completely dissolved. Then add maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester and continue stirring for 6 min. Add pretreated methyl methacrylate (triethoxysilyl) solution and stir for 6 min. The addition time is controlled at 4 min. Finally, add pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution and stir for 6 min until completely dissolved.
[0035] The azo initiator solution in step (4) is prepared by mixing 2,2'-azobis(2-methylpropylimidazolium) hydrochloride with deionized water to obtain a 1% mass concentration 2,2'-azobis(2-methylpropylimidazolium) hydrochloride solution.
[0036] The ammonium persulfate solution mentioned in step (4) is prepared by mixing ammonium persulfate and deionized water evenly to obtain an ammonium persulfate solution with a mass concentration of 3%, and then purging with nitrogen gas for 5 minutes to remove oxygen.
[0037] The sodium bisulfite solution mentioned in step (4) is prepared by mixing sodium bisulfite with deionized water to obtain a sodium bisulfite solution with a mass concentration of 1.6%, and then purging with nitrogen gas for 5 minutes to remove oxygen.
[0038] In step (4), the molar ratio of ammonium persulfate in the ammonium persulfate solution to sodium bisulfite in the sodium bisulfite solution is 1:1.2, and the molar ratio of 2,2'-azobis(2-methylpropylimidazolium) hydrochloride in the azo initiator solution to ammonium persulfate in the ammonium persulfate solution is 0.11:1.
[0039] The molar ratio of acrylamide in step (3) to ammonium persulfate in the ammonium persulfate solution in step (4) is 1:0.0008.
[0040] In step (4), the temperature is increased to 81℃ at a rate of 2℃ / min and held for 2h, and then decreased to 59℃ at a rate of 1.5℃ / min and held for 4h.
[0041] The post-treatment described in step (4) involves pouring the reaction solution into acetone while it is still hot, with a volume ratio of 1:3 between the reaction solution and acetone, so that the polymer precipitates out. Then, it is allowed to stand at room temperature for 33 minutes, filtered, washed three times with acetone, and finally vacuum dried at 57°C and -0.09 MPa for 8 hours. The mixture is then pulverized through an 80-mesh sieve to prepare the polymer thickener for fracturing.
[0042] Example 2 The preparation method of the polymer thickener for fracturing described in Example 2 consists of the following steps: (1) Add anhydrous sodium sulfate to methyl methacrylate (triethoxysilyl) and stir for 4 hours, then filter to prepare pretreated methyl methacrylate (triethoxysilyl) and mix it with anhydrous ethanol to prepare a pretreated methyl methacrylate (triethoxysilyl) solution. (2) Mix 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate with deionized water, then add sodium bicarbonate solution to adjust the pH of the system to 7.0, and purge with nitrogen to remove oxygen, to prepare a pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution; (3) Under nitrogen purging, deionized water was added to the reaction vessel, followed by the addition of acrylamide, maleic acid mono[2(1-oxo-2-propenyl)oxyethyl] ester, pretreated methacrylate (triethoxysilyl) methyl ester solution, and pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate solution. The mixture was stirred until completely dissolved to obtain an aqueous phase. (4) Under a nitrogen atmosphere, the aqueous phase reaction temperature prepared in step (3) is controlled at 13°C. Then, the azo initiator solution is added at once and stirred for 30s. Then, the ammonium persulfate solution is added at once and stirred for 30s. Finally, the sodium bisulfite solution is added at once and stirred for 30s. Nitrogen gas is stopped. The reaction system is heated to 80°C and kept at that temperature for 2h. Then, the temperature is lowered to 58°C and kept at that temperature for 4h. After the reaction is completed, the polymer thickener for fracturing is prepared by post-treatment. The molar ratio of acrylamide in step (3), maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester, pretreated methacrylate (triethoxysilyl) methyl methacrylate in step (1), and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate in step (2) is 1.4 : 0.1 : 0.3 : 0.15.
[0043] In step (1), the mass ratio of methyl methacrylate (triethoxysilyl) to anhydrous sodium sulfate is 2:1.
[0044] In step (1), the CAS number of methyl methacrylate (triethoxysilyl) is 5577-72-0, and its structural formula is [insert structural formula here]. .
[0045] In step (1), anhydrous ethanol and pretreated methyl methacrylate (triethoxysilyl) are mixed evenly at a mass ratio of 1:2 to prepare a pretreated methyl methacrylate (triethoxysilyl) solution.
[0046] In step (2), 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate and deionized water were stirred at 200 r / min for 5 min at room temperature in a mass ratio of 1:0.7. Then, a 5% sodium bicarbonate solution was added to adjust the pH of the system to 7.0. Nitrogen gas was then purged for 30 min to remove oxygen, thus preparing a pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution.
[0047] In step (2), the CAS number of 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate is 62723-61-9, and its structural formula is […]. .
[0048] In step (3), the CAS number of maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester is 19201-36-6, and its structural formula is as follows: .
[0049] In step (3), the mass ratio of acrylamide, maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester, pretreated methacrylate (triethoxysilyl) methyl methacrylate in step (1), and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate in step (2) to deionized water in step (3) is 1:4.
[0050] In step (3), the stirring speed is 200 r / min. Add acrylamide and stir until completely dissolved. Then add maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester and continue stirring for 5 min. Add pretreated methyl methacrylate (triethoxysilyl) solution and stir for 7 min. The addition time is controlled at 5 min. Finally, add pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution and stir for 5 min until completely dissolved.
[0051] The azo initiator solution in step (4) is prepared by mixing 2,2'-azobis(2-methylpropylimidazolium) hydrochloride with deionized water to obtain a 1% mass concentration 2,2'-azobis(2-methylpropylimidazolium) hydrochloride solution.
[0052] The ammonium persulfate solution mentioned in step (4) is prepared by mixing ammonium persulfate and deionized water evenly to obtain an ammonium persulfate solution with a mass concentration of 3%, and then purging with nitrogen gas for 5 minutes to remove oxygen.
[0053] The sodium bisulfite solution mentioned in step (4) is prepared by mixing sodium bisulfite with deionized water to obtain a sodium bisulfite solution with a mass concentration of 1.6%, and then purging with nitrogen gas for 5 minutes to remove oxygen.
[0054] In step (4), the molar ratio of ammonium persulfate in the ammonium persulfate solution to sodium bisulfite in the sodium bisulfite solution is 1:1.2, and the molar ratio of 2,2'-azobis(2-methylpropylimidazolium) hydrochloride in the azo initiator solution to ammonium persulfate in the ammonium persulfate solution is 0.11:1.
[0055] The molar ratio of acrylamide in step (3) to ammonium persulfate in the ammonium persulfate solution in step (4) is 1:0.0008.
[0056] In step (4), the temperature is increased to 80℃ at a rate of 2℃ / min and held for 2h, and then decreased to 58℃ at a rate of 1.5℃ / min and held for 4h.
[0057] The post-treatment described in step (4) involves pouring the reaction solution into acetone while it is still hot, with a volume ratio of 1:3 between the reaction solution and acetone, so that the polymer precipitates out. Then, it is allowed to stand at room temperature for 30 minutes, filtered, washed three times with acetone, and finally vacuum dried at 55°C and -0.09 MPa for 8 hours. The mixture is then pulverized through an 80-mesh sieve to prepare the polymer thickener for fracturing.
[0058] Example 3 The preparation method of the polymer thickener for fracturing described in Example 3 consists of the following steps: (1) Add anhydrous sodium sulfate to methyl methacrylate (triethoxysilyl) and stir for 4.5 hours, then filter to prepare pretreated methyl methacrylate (triethoxysilyl) and mix it with anhydrous ethanol to prepare a pretreated methyl methacrylate (triethoxysilyl) solution. (2) Mix 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate with deionized water, then add sodium bicarbonate solution to adjust the pH of the system to 7.0, and purge with nitrogen to remove oxygen, to prepare a pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution; (3) Under nitrogen purging, deionized water was added to the reaction vessel, followed by the addition of acrylamide, maleic acid mono[2(1-oxo-2-propenyl)oxyethyl] ester, pretreated methacrylate (triethoxysilyl) methyl ester solution, and pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate solution. The mixture was stirred until completely dissolved to obtain an aqueous phase. (4) Under a nitrogen atmosphere, the aqueous phase reaction temperature prepared in step (3) is controlled at 15°C. Then, the azo initiator solution is added at once and stirred for 35s. Then, the ammonium persulfate solution is added at once and stirred for 35s. Finally, the sodium bisulfite solution is added at once and stirred for 35s. Nitrogen gas is stopped. The reaction system is heated to 82°C and kept at that temperature for 2h. Then, the temperature is lowered to 60°C and kept at that temperature for 4h. After the reaction is completed, the polymer thickener for fracturing is prepared by post-treatment. The molar ratio of acrylamide in step (3), maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester, pretreated methacrylate (triethoxysilyl) methyl methacrylate in step (1), and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate in step (2) is 1.5 : 0.2 : 0.2 : 0.2.
[0059] In step (1), the mass ratio of methyl methacrylate (triethoxysilyl) to anhydrous sodium sulfate is 2:1.
[0060] In step (1), the CAS number of methyl methacrylate (triethoxysilyl) is 5577-72-0, and its structural formula is [insert structural formula here]. .
[0061] In step (1), anhydrous ethanol and pretreated methyl methacrylate (triethoxysilyl) are mixed evenly at a mass ratio of 1:2 to prepare a pretreated methyl methacrylate (triethoxysilyl) solution.
[0062] In step (2), 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate and deionized water were stirred at 200 r / min for 7 min at room temperature in a mass ratio of 1:0.7. Then, a 5% sodium bicarbonate solution was added to adjust the pH of the system to 7.0. Nitrogen gas was then purged for 35 min to remove oxygen, thus preparing a pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution.
[0063] In step (2), the CAS number of 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate is 62723-61-9, and its structural formula is […]. .
[0064] In step (3), the CAS number of maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester is 19201-36-6, and its structural formula is as follows: .
[0065] In step (3), the mass ratio of acrylamide, maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester, pretreated methacrylate (triethoxysilyl) methyl methacrylate in step (1), and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate in step (2) to deionized water in step (3) is 1:4.
[0066] In step (3), the stirring speed is 200 r / min. Add acrylamide and stir until completely dissolved. Then add maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester and continue stirring for 7 min. Add pretreated methyl methacrylate (triethoxysilyl) solution and stir for 5 min. The addition time is controlled at 4 min. Finally, add pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution and stir for 7 min until completely dissolved.
[0067] The azo initiator solution in step (4) is prepared by mixing 2,2'-azobis(2-methylpropylimidazolium) hydrochloride with deionized water to obtain a 1% mass concentration 2,2'-azobis(2-methylpropylimidazolium) hydrochloride solution.
[0068] The ammonium persulfate solution mentioned in step (4) is prepared by mixing ammonium persulfate and deionized water evenly to obtain an ammonium persulfate solution with a mass concentration of 3%, and then purging with nitrogen gas for 5 minutes to remove oxygen.
[0069] The sodium bisulfite solution mentioned in step (4) is prepared by mixing sodium bisulfite with deionized water to obtain a sodium bisulfite solution with a mass concentration of 1.6%, and then purging with nitrogen gas for 5 minutes to remove oxygen.
[0070] In step (4), the molar ratio of ammonium persulfate in the ammonium persulfate solution to sodium bisulfite in the sodium bisulfite solution is 1:1.2, and the molar ratio of 2,2'-azobis(2-methylpropylimidazolium) hydrochloride in the azo initiator solution to ammonium persulfate in the ammonium persulfate solution is 0.11:1.
[0071] The molar ratio of acrylamide in step (3) to ammonium persulfate in the ammonium persulfate solution in step (4) is 1:0.0008.
[0072] In step (4), the temperature is increased to 82℃ at a rate of 2℃ / min and held for 2h, and then decreased to 60℃ at a rate of 1.5℃ / min and held for 4h.
[0073] The post-treatment described in step (4) involves pouring the reaction solution into acetone while it is still hot, with a volume ratio of 1:3 between the reaction solution and acetone, so that the polymer precipitates out. Then, it is allowed to stand at room temperature for 35 minutes, filtered, washed three times with acetone, and finally vacuum dried at 60°C and -0.09 MPa for 8 hours. The mixture is then pulverized through an 80-mesh sieve to prepare the polymer thickener for fracturing.
[0074] Comparative Example 1 The only difference between the preparation method of the fracturing polymer thickener described in Comparative Example 1 and Example 1 is that maleic acid mono[2(1-oxo-2-propenyl)oxyethyl] ester is not added in step (3); the molar ratio of acrylamide in step (3), pretreated methyl methacrylate (triethoxysilyl) in step (1), and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate in step (2) is 1.45 : 0.25 : 0.17.
[0075] Comparative Example 2 The only difference between the preparation method of the fracturing polymer thickener described in Comparative Example 2 and Example 1 is that the pretreated methyl methacrylate (triethoxysilyl) solution is not added in step (3); the molar ratio of acrylamide, maleic acid mono[2(1-oxo-2-propenyl)oxyethyl] ester, and 2-[[2-(methacryloyloxy)ethyl] dimethylammonium] acetate in step (2) is 1.45 : 0.15 : 0.17.
[0076] Comparative Example 3 The only difference between the preparation method of the fracturing polymer thickener described in Comparative Example 3 and Example 1 is that the pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution is not added in step (3); the molar ratio of acrylamide, maleic acid mono[2(1-oxo-2-propenyl)oxyethyl] ester, and pretreated methacrylate (triethoxysilyl) methyl ester in step (1) is 1.45 : 0.15 : 0.25.
[0077] The fracturing polymer thickeners prepared in Examples 1-3 and Comparative Examples 1-3 were formulated into 0.50 wt% solutions, and their performance at 25°C for 170 seconds was tested. -1 120℃, 170s -1 and 160℃, 170s -1 The apparent viscosity was measured; the results are shown in Table 1.
[0078] Table 1 Apparent viscosity of polymer thickeners at room temperature and high temperature
[0079] As shown in Table 1, the polymer thickeners prepared in Examples 1-3 of this application have excellent temperature resistance compared with Comparative Examples 1-3.
[0080] The fracturing polymer thickeners prepared in Examples 1-3 and Comparative Examples 1-3 were formulated into 0.5 wt% solutions and subjected to fracturing at 25°C for 170 seconds. -1 The apparent viscosity was tested after 4.0 h of shearing; the results are shown in Table 2.
[0081] Table 2 Apparent viscosity of polymer thickener under shear conditions
[0082] As shown in Table 2, the polymer thickeners prepared in Examples 1-3 of this application have excellent shear resistance compared with Comparative Examples 1-3.
[0083] The fracturing polymer thickeners prepared in Examples 1-3 and Comparative Examples 1-3 were formulated into 0.5 wt% solutions. NaCl was added until the NaCl concentration in the system reached 50 g / L. The mixture was then subjected to fracturing at 25°C for 170 s. -1 The apparent viscosity was tested; the results are shown in Table 3.
[0084] Table 3 Apparent viscosity of polymer thickeners under high salt conditions
[0085] As shown in Table 3, the polymer thickeners prepared in Examples 1-3 of this application have excellent salt resistance compared with Comparative Examples 1-3.
[0086] The fracturing polymer thickeners obtained in Examples 1-3 and Comparative Examples 1-3 were formulated into a 0.5 wt% high-salt fluid (the solvent was prepared using simulated formation water with a salinity of 5*10). 4 (mg / L), stir until completely dissolved, let stand to defoam, add zirconium lactate crosslinking agent to the base liquid, the amount added is 0.3% based on the mass of the base liquid, use a stirrer at 400 r / min, at 140℃, crosslinking reaction for 2 h, test the gel strength of the formed gel, the results are shown in Table 4.
[0087] Ammonium persulfate was added to the formed gel at a concentration of 0.04 wt%. The gel was broken up at 140°C for 6 hours. The broken gel was then cooled to 25°C and subjected to further treatment at 25°C for 170 seconds. -1 The apparent viscosity of the gelling liquid was tested under the specified conditions, and the results are shown in Table 4.
[0088] Centrifuge 50 mL of the gel breaking solution at 3000 r / min for 35 min, pour off the supernatant, wash the gel breaking container with water and pour it back into the centrifuge tube, centrifuge at 3000 r / min for 35 min, then pour off the supernatant again, place the centrifuge tube in an oven to dry to constant weight, and divide the mass of the residue by the amount of fracturing fluid used to obtain the fracturing fluid residue content. The results are shown in Table 4.
[0089] Table 4. Application Effects of Polymer Thickeners for Fracturing
[0090] As shown in Table 4, the polymer thickeners prepared in Examples 1-3 of this application, compared with Comparative Examples 1-3, form gels with high strength when applied to fracturing fluids, and can break down quickly with less residue after breaking down, thus proving that they cause less damage to the formation.
[0091] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A method for preparing a polymer thickener for fracturing, characterized in that: It consists of the following steps: (1) Add anhydrous sodium sulfate to methyl methacrylate (triethoxysilyl) and stir for 4-4.5 hours, then filter to prepare pretreated methyl methacrylate (triethoxysilyl) and mix it with anhydrous ethanol to prepare a pretreated methyl methacrylate (triethoxysilyl) solution. (2) Mix 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate with deionized water, then add sodium bicarbonate solution to adjust the pH of the system to 7.0, and purge with nitrogen to remove oxygen, to prepare a pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution; (3) Under nitrogen purging, deionized water was added to the reaction vessel, followed by the addition of acrylamide, maleic acid mono[2(1-oxo-2-propenyl)oxyethyl] ester, pretreated methacrylate (triethoxysilyl) methyl ester solution, and pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate solution. The mixture was stirred until completely dissolved to obtain an aqueous phase. (4) Under a nitrogen atmosphere, the aqueous phase reaction temperature prepared in step (3) is controlled at 13-15℃. Then, the azo initiator solution is added at once and stirred for 30-35s. Then, the ammonium persulfate solution is added at once and stirred for 30-35s. Finally, the sodium bisulfite solution is added at once and stirred for 30-35s. Nitrogen gas is stopped. The reaction system is heated to 80-82℃ and kept at that temperature for 2h. Then, the temperature is lowered to 58-60℃ and kept at that temperature for 4h. After the reaction is completed, the polymer thickener for fracturing is prepared by post-treatment. The molar ratio of acrylamide in step (3), maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester, pretreated methacrylate (triethoxysilyl) methyl methacrylate in step (1), and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate in step (2) is 1.4-1.5 : 0.1-0.2 : 0.2-0.3 : 0.15-0.
2.
2. The method for preparing the polymer thickener for fracturing according to claim 1, characterized in that: In step (1), the mass ratio of methyl methacrylate (triethoxysilyl) to anhydrous sodium sulfate is 2:1; In step (1), the CAS number of methyl methacrylate (triethoxysilyl) is 5577-72-0, and its structural formula is [insert structural formula here]. .
3. The method for preparing the polymer thickener for fracturing according to claim 1, characterized in that: In step (1), anhydrous ethanol and pretreated methyl methacrylate (triethoxysilyl) are mixed evenly at a mass ratio of 1:2 to prepare a pretreated methyl methacrylate (triethoxysilyl) solution.
4. The method for preparing the polymer thickener for fracturing according to claim 1, characterized in that: In step (2), 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate and deionized water are stirred at 200 r / min for 5-7 min at room temperature in a mass ratio of 1:0.
7. Then, a 5% sodium bicarbonate solution is added to adjust the pH of the system to 7.
0. Nitrogen gas is then purged for 30-35 min to remove oxygen, thus preparing a pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution. In step (2), the CAS number of 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate is 62723-61-9, and its structural formula is [insert structural formula here]. .
5. The method for preparing the polymer thickener for fracturing according to claim 1, characterized in that: In step (3), the CAS number of maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester is 19201-36-6, and its structural formula is as follows: .
6. The method for preparing the polymer thickener for fracturing according to claim 1, characterized in that: In step (3), the mass ratio of acrylamide, maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester, pretreated methacrylate (triethoxysilyl) methyl methacrylate in step (1), and 2-[[2-(methacryloyloxy)ethyl]dimethylammonium] acetate in step (2) to deionized water in step (3) is 1:
4.
7. The method for preparing the polymer thickener for fracturing according to claim 1, characterized in that: In step (3), the stirring speed is 200 r / min. Add acrylamide and stir until completely dissolved. Then add maleic acid mono[2(1-oxo-2-propenyl)oxoethyl] ester and continue stirring for 5-7 min. Add pretreated methyl methacrylate (triethoxysilyl) solution and stir for 5-7 min. The addition time is controlled at 4-5 min. Finally, add pretreated 2-[[2-(methacryloyloxy)ethyl]dimethylammonium]acetate solution and stir for 5-7 min until completely dissolved.
8. The method for preparing the polymer thickener for fracturing according to claim 1, characterized in that: The azo initiator solution in step (4) is prepared by mixing 2,2'-azobis(2-methylpropylimidazolium) hydrochloride with deionized water to obtain a 1% (w / w) 2,2'-azobis(2-methylpropylimidazolium) hydrochloride solution. The ammonium persulfate solution mentioned in step (4) is prepared by mixing ammonium persulfate and deionized water evenly to obtain an ammonium persulfate solution with a mass concentration of 3%, and then purging with nitrogen gas for 5 minutes to remove oxygen; The sodium bisulfite solution mentioned in step (4) is prepared by mixing sodium bisulfite with deionized water to obtain a sodium bisulfite solution with a mass concentration of 1.6%, and then purging with nitrogen gas for 5 minutes to remove oxygen.
9. The method for preparing the polymer thickener for fracturing according to claim 1, characterized in that: In step (4), the molar ratio of ammonium persulfate in the ammonium persulfate solution to sodium bisulfite in the sodium bisulfite solution is 1:1.2, and the molar ratio of 2,2'-azobis(2-methylpropylimidazolium) hydrochloride in the azo initiator solution to ammonium persulfate in the ammonium persulfate solution is 0.11:
1. The molar ratio of acrylamide in step (3) to ammonium persulfate in the ammonium persulfate solution in step (4) is 1:0.0008.
10. The method for preparing the polymer thickener for fracturing according to claim 1, characterized in that: In step (4), the temperature is increased to 80-82℃ at a rate of 2℃ / min and held for 2h, and then decreased to 58-60℃ at a rate of 1.5℃ / min and held for 4h. The post-treatment described in step (4) involves pouring the reaction solution into acetone while it is still hot, with a volume ratio of 1:3 between the reaction solution and acetone, so that the polymer precipitates out. Then, it is allowed to stand at room temperature for 30-35 minutes, filtered, washed three times with acetone, and finally vacuum dried at 55-60℃ and -0.09MPa for 8 hours. The mixture is then pulverized through an 80-mesh sieve to prepare the polymer thickener for fracturing.
Citation Information
Patent Citations
Novel viscoelastic particle oil displacement agent and preparation method thereof
CN101775275B
High-temperature-resistant instant thickening agent for fracturing fluid and preparation method of thickening agent
CN112266779A
Temperature-resistant and salt-resistant multi-component polymerization thickening agent and preparation method thereof
CN113788911A